Halogens in proto-Iceland plume basalts - Tomlinson, Emma (My University, 2025)
Melt inclusions in olivine phenocrysts from high 3He/4He proto-Iceland plume (PIP) basalts from Baffin Island and West Greenland have elevated Br/Cl ratios, extending to values significantly above those found in mid-ocean ridge basalt (MORB) and ocean island basalt (OIB). Chlorine isotope compositions are indistinguishable from MORB-source mantle and high Br/Cl occurs in the absence of geochemical indicators for serpentinite, altered oceanic crust or sediment. The highest Br/Cl occurs in melt inclusions from basalts with the highest 3He/4He. The high Br/Cl ratios are at the high end of the range of putative Earth-source meteorites (CI- and CM-type carbonaceous chondrites). The PIP melt inclusion compositions are consistent with the addition of a small volume of halogen-rich, high Br/Cl chondritic material to halogen-depleted, low Br/Cl mantle.
PUBLISHED
Keywords: Halogens, mantle, Baffin Island, West Greenland, basalt; Geochemistry